The Analysis of Promotion of Position Reviewed from Work Achievement, Work Experience and Competence Employee Work in PT. Pusat Penelitian Kelapa Sawit - Nurma Serliana (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2020)
This research was done in PT. Pusat Penelitian Kepala Sawit with the aim of research to analyzed the influenced of working performance, working experience and working competence toward on job promotion. This type of research used correlational research, the population were employees who worked in the company as many as 497 people, random sampling was the Slovin formula so that the number of samples amount of 83 respondents. Data sources used primary data and secondary data, data collection techniques by giving questionnaires. The data analysis technique used multiple linear regression, classic assumption test and hypothesis test. Based on the results of the studied showed that simultaneously and partially working performance, working experience and working competency have positive and significant effected toward on job promotion. The adjusted R square coefficient (R2) of 0.862 showed that promotion in the company able to be explained by work performance, work experience, and promotion of 86.20%, and the other amount of 13.8% could be explained by other variables did not examined such as training, education, performance and so on.